PEMBERDAYAAN SEMANGAT TOLERANSI BERAGAMA DALAM KOMUNITAS PELAYANAN DIALOG ANTAR-AGAMA DI KECAMATAN KEPANJEN, MALANG - Effendi, Yulius Rustan (Universitas Sanata Dharma, 2023)
Empowerment of awareness and the meaning of life of religious tolerance is a very important activity to be given to the community. The aim is to develop broad insights and understanding, to form tolerant behavior that is shown through concrete actions that support the creation of a safe, peaceful, harmonious life in an integrative society based on multiculturalism values. This tolerant life empowerment activity is a real effort to overcome various forms of conflict due to intolerance in society. Therefore, it is necessary to carry out community empowerment activities in the community of inter-religious dialogue services to build awareness of living as a tolerant nation and state. The method used in this community service activity is the socialization of empowerment (lectures) and simulations (dialogue/fraternal sharing and real action) guided by the speakers. The subjects in this empowerment activity are the people who join the Inter-religious Dialogue Service Community, especially the Inter-religious Dialogue Service Community of St. Ignasius Loyola in the Kepanjen Parish area, Malang, with a total of 80 participants. As a result of this empowerment of religious tolerance, the community has broad knowledge and understanding regarding the importance of a safe and harmonious life, and is able to build an open and adaptive culture of religious tolerance.